Land-Based Education for Northern Youth: Exploring the Impacts of On-the-Land Camps in the Northwest Territories - Woodworth, Stephanie Marianne (Université d'Ottawa / University of Ottawa, 2025)
Ongoing extractive research and educational systems continue to perpetuate colonial narratives of northern Indigenous communities and the Land which ignore the rights, perspectives, and values of Indigenous Peoples in arctic and subarctic regions around the world, such as the Northwest Territories (NWT). Additionally, Indigenous Peoples face rapid environmental and sociocultural changes that disrupt access to traditional places and practices and limit cross-generational knowledge transfer and decreases opportunities for youth to connect with the Land. Land-based programs aim to provide Indigenous and non-Indigenous youth with spaces to learn about and connect with the Land. However, limited research exists on the experiences of youth in land-based programs, particularly regarding their potential to foster leadership and Land Stewardship among northern youth. Additionally, there is a lack of research documenting the impacts of on-the-land camps as spaces for land-based research projects. Grounded in an Indigenous Research Paradigm (IRP) methodology and Land Stewardship theoretical framework, this land-based research addresses the forementioned gaps in three manuscripts: (M1) "It's not being 'on-the-land'; it's like we are a part of the Land.": Indigenous Youth share visual stories at "on-the-land" camps in the Dehcho; (M2) "A connection with the Land will help youth protect it": Empowering northern youth as Land Stewards through land-based programs in the Northwest Territories and (M3) "Just being on-the-land, the traditional way, eating the food off it. I couldn't ask for a better community to do that in": On-the-land camps as a space for collaborative, reciprocal land-based research. An adapted photovoice method was used to support northern youth to share visual stories of their experiences at four on-the-land camps in the NWT. This research documents the ways the youth were (re)connecting with the Land (M1) and empowered as leaders through Land Stewardship values and practices (M2) at on-the-land camps. By analysing stories from Ka'a'gee Tu, also spelled as K'ágee Tue First Nation (KTFN), youth, Tarek Leahy-Chicot, I provide a reflective examination of this collaborative land-based research to explore holistic meanings and stories of the Land (M3). The results show that land-based programs, like on-the-land camps, are transformative and healing spaces for building relationships between youth and the Land and empowering them as leaders and Land Stewards. Additionally, on-the-land camps are effective spaces for conducting collaborative, reciprocal land-based research. Throughout the dissertation, I include my own personal photographs and poetry as section breaks to create space for the reader to stop, pause, and breathe, and allow for moments of reflection about the ideas shared. This research was conducted and written with love, care, respect, and reciprocity, embedded with my emotions and self-reflection, and it is an act of nurturing and honouring all my relationships.
Keywords: Land-based education; Youth; Photovoice; Land Stewardship; Arctic